COUPLED HEAT AND MOISTURE TRANSFER IN UNSATURATED SOIL FOR THE MODELING OF SHALLOW HORIZONTAL GROUND LOOPS - Wu, Ray (My University, 2014)
INTRODUCTION In recent decades, ground-source heat pump (GSHP) systems have received considerable attention as an energy efficient technology for residential and commercial heating and cooling. Approximately 50,000 GSHP systems are sold each year in the United States (Do and Haberl, 2010). As one of the fastest growing applications of alternative energy, a primary appeal of GSHP systems is their efficiency and widespread geographic applicability. GSHP systems are efficient because the geothermal exchange occurs through the sustainable transfer of stored thermal energy. GSHP systems can also be implemented worldwide because the ground acts as an effective thermal source and sink. Natural ground temperatures become relatively stable with increasing depth and are closer to room temperature (e.g., 20 C) than air temperature during the year. Noteworthy recognition of the promising potential of GSHP systems was publicized during the late 20th century as government reports by the United States Environmental Protection Agency and Natural Resources Canada stated, respectively, that ?GSHPs are the most energy efficient, environmentally clean, and cost-effective systems available? (US EPA, 1993) and that ?There is unlikely to be a potentially larger mitigating effect on greenhouse gas emissions and the resulting global warming impact of buildings from any other current, market available single technology, than from GSHPs? (Caneta Research, 1999). In comparison to traditional heating, ventilation, and air conditioning (HVAC) systems, GSHP systems offer benefits of reduced greenhouse gas emissions, high reliability, low maintenance, and lower energy, operating, and life-cycle costs (Inalli and Esen, 2005; Tarnawski et al., 2009; Congedo et al., 2012). Despite these advantages, however, several barriers continue to hinder increased implementation of GSHP systems. Important barriers include the high initial capital costs of GSHP systems and the lack of consumer knowledge and/or confidence in GSHP system benefits (Hughes, 2008). The high initial investment and lack of consumer confidence in GSHP systems are, in part, related to the design of the GSHP?s ground loop. As shown in Table 1-1, the ground loop is generally the most expensive component of a GSHP system. Cane and Forgas (1991) estimated that the length of ground loops used in GSHP applications were oversized by about 10% to 30% in the North American market. The length of ground loops may still be oversized due to prevalent use of rule of thumbs (i.e., certain length of trench per quantity of load) and conservative estimates of subsurface properties (McQuay International, 2002; ASHRAE, 2007; Remund and Carda, 2009). Conservatively designed ground loops safeguard against worst-case scenarios but result in inefficient and uneconomical GSHP systems. Shallow horizontal ground loops have potential to provide an effective compromise between efficiency and cost if the thermal performance of the ground loop is improved and the material, installation, and operating costs are reduced. By improving the design of ground loops, GSHP systems can be optimized and have better performance and lower capital investments. This thesis focuses on using energy geotechnics to improve the design of shallow horizontal ground loops. Energy geotechnics is an emerging discipline in which engineers and scientists employ principles of geotechnical engineering and the physical sciences of geology, physics, and chemistry for the advancement and design of energy-related systems, including renewables. In this study, the mechanisms and properties that govern thermal and hydraulic behavior of unsaturated soil are applied to predict coupled heat and moisture flow associated with operation of a shallow horizontal ground loop. More specifically, experimentally determined thermal conductivity dryout curves (TCDCs) and soil-water characteristic curves (SWCCs) were coupled in finite-element models to simulate temporal and spatial variations of soil surrounding horizontal ground loops. Results from the simulations were used to estimate the required total length of ground loop attached to a GSHP system using a heat pump with nominal 10.55-kW capacity and coefficient of performance (COP) of 4. Changes in the required total length of ground loop as well as associated costs are compared between models that were simulated with a soil?s TCDC versus similar models that were simulated with a conservative value of soil thermal conductivity (?soil). Chapter 2 contains background information about GSHP systems, the importance of ?soil and TCDCs, and methods for experimental determination of TCDCs. Chapter 3 discusses the selected materials, the methods used to determine material properties, and setup of a two-dimensional horizontal ground loop model based on finite-element analysis. Chapter 4 presents results and analysis of the model simulations. Chapter 5 summarizes conclusions drawn from model results and discusses recommended future work to improve modeling of shallow horizontal ground loops. In the appendices, a draft of an ASTM International standard for experimental determination of thermal resistivity dryout curves (TRDCs) is included (Appendix A); a discussion on testing ?soil at elevated temperatures is included (Appendix B); and an overview of finite-modeling with SVOffice is presented (Appendix C).